MONTHLY PUBLIC SANITATION EXERCISE REGIMENS: A PERSPECTIVE ON SUSTAINABILITY OF LABOUR AND HYGIENE - Azuwike, Okechi Dominic; Eboh, Emmanuel A (African Journal of Social and Behavioural Sciences, 2020)
The idea of public participation in clean-up exercises on a monthly cycle has caught in Africa probably signalling a failure of municipal or other authorities in managing sanitation and therefore a certain imperative in conscripting the public. The theory of sustainability guided the discourse. The present effort assesses the sustainability of this development in the light of suitability of deployment of the public as manpower for this and the value of the ultimately achieved hygiene. It does this through participant observation of this exercise in 10 different locations in Imo State and review of literatures. The study found that the deployment of highly trained professionals in basic janitorial activities and menial engagement not only fails to optimize the value of their specialized skills but prevents the development of janitorial activities as a professional engagement. The implementation cost is also prohibitive given its coercive, command and control orientation while its achievement in the area of hygiene is poor given that it promotes a culture of waste storage and an orientation of living with stowed waste all month long. The avalanches of evacuated waste on the fixed „clean up‟ days also outstrip the management capacity of waste disposal systems. The study suggests mainstreaming waste management into daily life rather than monthly regimens.